THE DIPOLAR FRENKEL EXCITONIC INSULATOR PHASE OF AN IMPURITY IN A LIQUID SOLVENT - RESULTS - Winn, M; Logan, D (1993)
In a previous paper the authors have developed a mean field theory for the dipolar Frenkel excitonic insulator (EI) phase of an impurity at infinite dilution in a liquid solvent or disordered matrix, a situation of experimental relevance. Based on this, they here present numerical results for the location of the EI transition, and the impurity dipole moment in the dipolar EI phase, using linear classical liquid state theories. For a non-polar polarizable solvent, the authors consider impurity and solvent atoms of (i) identical hard-sphere diameter, and (ii) differing hard-sphere diameter. They also generalize the previously studied model to allow for dipolar polarizable solvent molecules, and present example results. The authors consider in particular the case of alkali metal atoms dissolved in methylamine, and conclude that a dipolar EI phase is possible for Li and Cs.